2020
DOI: 10.1364/josab.388470
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of spatiotemporal dynamics of a quadruple Gaussian laser beam in a relativistic ponderomotive magnetized plasma

Abstract: An investigation of the spatiotemporal dynamics of a quadruple Gaussian laser beam via plasma in the presence of an external magnetic field characterized by ponderomotive and relativistic nonlinearities is presented. The moment theory approach is used to study the second-order nonlinear differential equation analytically and numerically. The evolution of the beam width parameter determines the pulse dynamics, in both time and space. The spatial evolution at different pulse ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Investigations have been carried out to analyze the spatiotemporal evolution characteristics of quadruple Gaussian laser beams in the presence of an external magnetic field. The results indicate that selffocusing is reduced with increasing laser intensity, while gradual increments in plasma density, the time factor, and magnetic field intensity lead to enhanced self-focusing [40]. Similar studies have demonstrated the enhanced self-focusing nature of quadruple Gaussian beams [32].…”
Section: Introductionsupporting
confidence: 55%
“…Investigations have been carried out to analyze the spatiotemporal evolution characteristics of quadruple Gaussian laser beams in the presence of an external magnetic field. The results indicate that selffocusing is reduced with increasing laser intensity, while gradual increments in plasma density, the time factor, and magnetic field intensity lead to enhanced self-focusing [40]. Similar studies have demonstrated the enhanced self-focusing nature of quadruple Gaussian beams [32].…”
Section: Introductionsupporting
confidence: 55%
“…Self focusing of the laser beams in different nonlinear media has been a hot topic of research since its discovery by Askaryan [11]. In past few years a vast literature has been reported by researchers from all over the globe on various aspects of this phenomenon [20][21][22][23]. Early seminal work of Sodha et al [24] gave a gravest blow to the investigation of this phenomenon for intense laser beams interacting with plasmas in different environments and regimes.…”
Section: Introductionmentioning
confidence: 99%
“…super Gaussian [3], cosh-Gaussian [4], Laguerre-Gaussian [5], Hermite-Gaussian [6], quadruple Gaussian [7], ๐‘ž๐‘ž-Gaussian [8], Bessel-Gaussian [9] and Hermite-cosh-Gaussian [10] beams due to their specific characteristics.…”
mentioning
confidence: 99%